Shell finite elements, with emphasis on strategies used within Elmer software - Malinen, Mika (Rakenteiden mekaniikka, 2017)
The best way to handle finite element discretization of structural shell equationsis still a subject of discussion. This article presents some viewpoints and reviews innovationswhich have recently been taken into use in connection with the implementation of new shell finite elements into the open source finite element software Elmer.